Wildcat population density on the Etna volcano, Italy: a comparison of density estimation methods. (22nd April 2014) - Anile, S.; Ragni, B.; Randi, E.; Mattucci, F.; Rovero, F.
Abstract The European wildcat is an elusive felid that is declining across its range. Sicily hosts a distinctive insular wildcat population, the conservation of which requires much better ecological knowledge than is currently available, particularly population density. We simultaneously used two noninvasive methods (camera‐trapping and scat‐collection) to estimate the population density of wildcats on the Etna volcano. We conducted genetic analyses to identify individuals and to detect potential hybridization with the domestic cat. We analyzed individual capture‐histories from camera‐trapping and scat‐collection using the spatially explicit capture‐recapture (SECR) model. Furthermore, we applied the random encounter model (REM), which does not require individual identification, to the camera‐trapping data. We identified 14 wildcats from 70 photographic detections (6.48 detections/100 trap‐days) obtained from 1080 camera‐trapping days over 4 months, and we estimated to have identified all the individuals living in the study area (10.9 km−2). On the contrary, we identified 10 wildcats from 14 out of 39 scats collected from 391 km of transects walked. The estimated densities (individuals km−2 ± se) were 0.32 ± 0.1 (SECR camera‐trapping), 1.36 ± 0.73 (SECR scat‐collection) and 0.39 ± 0.03 (REM). The population density estimates obtained from SECR camera‐trapping and REM overlapped, although we recommend care when applying the latter. The SECR scat‐collection gave the highest population density (and less precise) estimates because of the low number of capture and recaptures; however, the population size estimated with this method matched the number of individuals photographed. The population density of the wildcat in Etna falls in the medium‐high range of those reported in literature, highlighting the role of this ecosystem for the long‐term conservation of the wildcat in Sicily. Camera‐trapping is confirmed as a useful tool to assess the wildcat population density and, in this case, was complemented by the genetic analysis that confirmed individual identity.